Newborn Screening-A Bolstering Step towards Quality Health in Neonates - Suprava Patel; Ritupriya; Phalguni Padhi; Tripty Naik; Rachita Nanda; Eli Mohapatra; Sarita Agrawal (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Newborn Screening (NBS) is considered the need of the hour for quality health in neonates. It is also important to understand that the rising trend of prevalence of inherited metabolic disorders and the various maternal factors that might influence genetic changes in the foetus inutero affecting the neonatal outcome. Aim: The primary objective of the study was to determine frequency of Congenital Hypothyroidism (CH) and Glucose6-Phosphate Dehydrogenase (G6PD) deficiency in a most approachable tertiary care hospital. The secondary objectives were to find out impact of maternal factors on the frequency of the disease and the impact of the disorder on the neonate's health. Materials and Methods: The cross-sectional study was conducted on 1282 neonates of 48 hours upto eight weeks of age. The Dried Blood Spot (DBS) specimens collected were analysed for Thyroid Stimulating Hormone (TSH) level and G6PD enzyme activity. Details of neonatal characteristics and antenatal history were documented. Prevalence of CH and G6PD deficiency was calculated and maternal and neonatal variables were analysed for association using Statistical Package for the Social Sciences (SPSS) version 20. Results: The prevalence of CH and G6PD were respectively 3.3/1000 and 6.6/1000 making the overall prevalence of metabolic disorders as 9.8/1000. A 27.3% had Low Birth Weight (LBW) and 62% had low Ponderal Index (PI). The odds for raised TSH was 6.62 times in sick neonates. The probability for high TSH in LBW babies was more by 94% and in female neonates by 18%. The neonates with higher TSH values depicted significant association with maternal age (p=0.016), gestational age (p=0.019) and maternal anaemia (p<0.001). Babies born by caesarean section showed twice the chances for screening positive for TSH. Conclusions: The high prevalence estimated in this study and association with maternal factors urges new queries and recommends an obligatory need for NBS program in this region.